Osteoprotegerin, RANKL, and Bone Turnover in Primary Hyperparathyroidism: The Effect of Parathyroidectomy and Treatment with Alendronate - Szymczak, J.; Bohdanowicz-Pawlak, A. (Hormone and Metabolic Research, 2013)
Receptor activator of nuclear factor-κB (RANK), RANK ligand (RANKL), and its decoy receptor osteoprotegerin (OPG) play key roles in regulating bone turnover. The OPG/RANKL/RANK system is regulated by many hormones and cytokines, among which parathormone (PTH) seems to be one of the most important. Primary hyperparathyroidism (PHPT) with chronic excess of PTH and enhanced bone resorption provides an opportunity to observe the relationships between PTH, OPG and RANKL. From a group of 63 patients with PHPT, 29 underwent effective parathyroidectomy (PTX) and 33 were treated with alendronate. After one year, bone mineral density (BMD) improved in both groups, but the biochemical disturbances and PTH returned to normal only after PTX. The baseline serum concentrations of OPG and RANKL were higher in PHPT patients than in healthy controls, whilst the OPG/RANKL-F ratio was lower. The mean OPG concentration did not change after PTX, and slightly increased after alendronate treatment despite the unchanged PTH. Twelve months after treatment, RANKL slightly declined in both groups and the ratio of OPG/RANKL consistently increased. Serum OPG and RANKL did not correlate with PTH before or after PTX or alendronate treatment. In conclusion, bone resorption in PHPT is accompanied by a high serum concentration of OPG and RANKL as well as a low OPG/RANKL ratio. Both parathyroidectomy and treatment with alendronate diminish bone resorption, and correct the OPG/RANKL ratio in favor of OPG, although the mechanisms of their actions are different. Serum OPG concentration does not depend directly on PTH.
Keywords: alendronate; hyperparathyroidism; RANKL; bone mineral density